Experimental determination of the time of concentration, Sapucajuba creek small watershed study (Research, Society and Development, 2021)
Time of concentration (tc) is a parameter that indicates the response time of a river catchment to a rainfall. Frequently, empirical equations are used to determination of tc for the design of the maximum flow. However, the determination of this response time by equations sometimes results in an erroneous application, that is, outside its field of validity. Thus, the present work aimed to determine tc in an experimental and simplified way in the Sapucajuba creek, from measurements in the field, with saline tracer, and to make a comparison with 13 empirical models, which require the morphometric characteristics of the small watershed. It was observed that they underestimated the time of concentration value, in general, by empirical models, overestimating the future project flow. DNOS (sandy-clay condition, intense vegetation, high absorption) was the most indicated model for the estimate of tc, that provided the lowest percentage error, 1.92%, compared to tc measured in the field. However, such error exceeded 70.00% by other models, showing great variability. Therefore, it is strongly recommended the determination of tc in field, that will provide a real result, contributing to the economic dimensioning of hydraulic-hydrological works and projects.